Components of brending and the application of artifical intelligence technologies in their implementation - Оleg Kovalchuk (Економічний форум)
The article examines the issue of branding components and the use of artificial intelligence technologies in their implementation. It has been established that the development and implementation of an effective branding strategy is one of the leading tasks of marketing activity. This task has not lost its relevance for a long time, and in connection with the development of new digital technologies and the formation of the digital economy, it acquires new challenges. It was established that digital tools and technologies open up new opportunities for specialists in the field of marketing, including branding. These new opportunities are both new channels and new methods of communication, as well as new technologies that marketers can use in their work. In particular, technologies related to the use of artificial intelligence are now attracting a lot of attention. The study of the components of branding is summarized and its main stages are highlighted: market and audience analysis, brand creation, brand strategy development, brand communication, brand management. It is emphasized that special attention needs to be paid to the implementation of the specified components of branding in the context of the active formation of digital information and communication tools, the development of neural networks and related artificial intelligence technologies, because they cause significant changes at various stages of branding, forming both additional challenges and obstacles, and and opening up new opportunities. By summarizing the views of scientists and practitioners, it was established that artificial intelligence can effectively help brand marketers in building a branding strategy, creating content, developing creative concepts, analyzing results and establishing relationships with consumers. The general conclusion is that, in general, artificial intelligence can perform a variety of analytical, search, creative tasks to support the effective operation of the brand and attract more consumers